2014
DOI: 10.1186/1472-6882-14-224
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of the mechanism of traditional Chinese medical prescription-Yiqihuoxue formula as an effective anti-fibrotic treatment for systemic sclerosis

Abstract: BackgroundSystemic sclerosis (SSc) is a connective tissue fibrotic disease for which there is no effective treatment. Traditional Chinese Medicine (TCM), such as the Yiqihuoxue formula used in Shanghai TCM-integrated Hospital, has shown the efficacy of anti-fibrosis in clinical applications. This study was aiming to dissect the anti-fibrotic mechanism of Yiqihuoxue treatment for SSc.MethodsBleomycin-induced mice and SSc dermal fibroblasts were treated with Yiqihuoxue decoction; NIH-3T3 fibroblasts were exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…The animals used in experiment were approved by the School of Life Sciences, Fudan University, China, and the animal protocols were performed in accordance with the approved guidelines. 21…”
Section: Establishment Of Skin Fibrosis Mouse Modelmentioning
confidence: 99%
“…The animals used in experiment were approved by the School of Life Sciences, Fudan University, China, and the animal protocols were performed in accordance with the approved guidelines. 21…”
Section: Establishment Of Skin Fibrosis Mouse Modelmentioning
confidence: 99%
“…The Yiqihuoxue formula was prepared as previously described15. pGL3-SBE 4 -Luc was a gift from Dr. Kiyoshi Higashi (Sumitomo Chemical Co., Ltd., Osaka, Japan), and consists of four short tandem repeats of the SBE oligonucleotide (GTCTAGAC) inserted into the pGL3 Basic vector35.…”
Section: Methodsmentioning
confidence: 99%
“…The other parts were immediately stored in liquid nitrogen. To evaluate skin sclerosis, a 4 μm section of skin was stained using hematoxylin and eosin; its thickness was then measured, using Image J (National Institutes of Health, Bethesda, MD, USA), on photographs taken in 10 microscopy fields (×100) at the site of maximum distance between the epidermal-dermal and dermal-subcutaneous fat junctions [11]. The mean AE SD of these measurements was then calculated.…”
Section: Histopathologymentioning
confidence: 99%
“…In particular, dose-dependent KBG treatment has been shown in vitro to inhibit collagen production from cultured fibroblasts of SSc patients' skin [10]. Recently, it was reported that yiqihuoxuetang, which contains astragali radix, suppressed collagen production and dermal sclerosis progression in a bleomycin (BLM)-induced mouse model of scleroderma [11].…”
Section: Introductionmentioning
confidence: 99%